THE CULTURAL DIMENSION - Cochran, Terry (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
A study of the relationship between culture and technology in the writings of Benjamin and Gramsci, with special reference to its impact on the notion of the nation state.